A critical appraisal of the evidence for the role of splenectomy in adults and children with ITP. (26th February 2018) - Rodeghiero, Francesco
Summary: In primary chronic immune thrombocytopenia, long‐term response to splenectomy, with 60% of patients enjoying a treatment‐free life, is higher when compared with rituximab and similar to that with continuous thrombopoietin‐receptor agonists (TPO‐RA) administration. Splenectomy should continue to be offered to patients failing initial treatments in the absence of increased surgery‐related risks. The higher lifelong safety concerns with splenectomy (increased risk of infection, shared in part with rituximab, and of thrombosis, in common with TPO‐RA) and a mortality <1–2%, justify postponing surgery to the chronic phase, when spontaneous remissions are rarer. Patients failing initial treatment with corticosteroids/intravenous immunoglobulin may use TPO‐RA (or rituximab in selected cases) as a bridge to surgery if they prefer to reconsider splenectomy later on, in case of no response, adverse effects or if sustained response after stopping TPO‐RA is not attained. Special considerations apply in children aged ≤5 years, with splenectomy playing a marginal role. The recent approval of TPO‐RA in children may represent a major advancement.